2016
DOI: 10.1080/10826084.2016.1188954
|View full text |Cite
|
Sign up to set email alerts
|

The Criminal Justice Experience of African American Cocaine Users in Arkansas

Abstract: Background African Americans are incarcerated at rates much higher than other racial and ethnic groups in the United States. Objectives We sought to qualitatively explore the relationships between ongoing involvement in the criminal justice system and continued drug use in a population of urban and rural African American cocaine users in a southern state. Methods Semi-structured qualitative interviews were conducted among African American cocaine users in Arkansas between 2010 and 2012. Participants reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The expansion of drug courts in rural areas, which have been shown to be associated with treatment use (Perron & Bright, 2008), could elevate awareness of treatment as an alternative to incarceration. On the other hand, our qualitative research conducted in the same areas where we conducted this quantitative study found that many African American/Black persons using cocaine are skeptical of the benefits of court-mandated treatment (Zaller et al, 2016). Third, the finding that perceptions of treatment effectiveness serve as a mediator suggests that public campaigns that further promote the benefits treatment might encourage treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of drug courts in rural areas, which have been shown to be associated with treatment use (Perron & Bright, 2008), could elevate awareness of treatment as an alternative to incarceration. On the other hand, our qualitative research conducted in the same areas where we conducted this quantitative study found that many African American/Black persons using cocaine are skeptical of the benefits of court-mandated treatment (Zaller et al, 2016). Third, the finding that perceptions of treatment effectiveness serve as a mediator suggests that public campaigns that further promote the benefits treatment might encourage treatment seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Rural experiences of the criminal justice system vary greatly: from, for example, the rates of prosecution and sentencing, to the spatial distribution of police institutions, courts, and correctional facilities. This subject has been examined within a range of different contexts (see, e.g., Austin, 1981;Bond-Maupin & Maupin, 1998;Campbell et al, 2014;Ferrazzi & Krupa, 2018;Romero, 2020;Steiner, 2005;Zaller et al, 2016). For example, the effects of legislation on the policing of rural youth have been found to be of limited success due to the situational contexts of rural regions, including geography, underdeveloped infrastructure, and restricted resources (Ricciardelli et al, 2017;Wright, 1997).…”
Section: The Rural Criminal Justice Systemmentioning
confidence: 99%
“…The policing and prevention of drug crime in rural areas can be a controversial issue. The so-called war on drugs in the United States has been criticized for unfairly targeting the poor and people of certain ethnicities, which holds true for rural areas as well (see, e.g., Abadie et al 2018;Shukla et al 2019;Zaller et al 2016). Police in Scotland have noted the difficulty in disrupting drug markets in certain rural areas as drug organizations from elsewhere can maintain "markets by proxy" in these areas (Clark et al 2020).…”
Section: Prevention Of Some Typical Rural Issuesmentioning
confidence: 99%